Shedding of syndecan-4 promotes immune cell recruitment and mitigates cardiac dysfunction after lipopolysaccharide challenge in mice. (November 2015) - Strand, Mari E.; Aronsen, Jan Magnus; Braathen, Bjørn; Sjaastad, Ivar; Kvaløy, Heidi; Tønnessen, Theis; Christensen, Geir; Lunde, Ida G.
Abstract: Inflammation is central to heart failure progression. Innate immune signaling increases expression of the transmembrane proteoglycan syndecan-4 in cardiac myocytes and fibroblasts, followed by shedding of its ectodomain. Circulating shed syndecan-4 is increased in heart failure patients, however the pathophysiological and molecular consequences associated with syndecan-4 shedding remain poorly understood. Here we used lipopolysaccharide (LPS) challenge to investigate the effects of syndecan-4 shedding in the heart. Wild-type mice (10 mg/kg, 9 h) and cultured neonatal rat cardiomyocytes and fibroblasts were subjected to LPS challenge. LPS increased cardiac syndecan-4 mRNA without altering full-length protein. Elevated levels of shedding fragments in the myocardium and blood from the heart confirmed syndecan-4 shedding in vivo. A parallel upregulation of ADAMTS1, ADAMTS4 and MMP9 mRNA suggested these shedding enzymes to be involved. Echocardiography revealed reduced ejection fraction, diastolic tissue velocity and prolonged QRS duration in mice unable to shed syndecan-4 (syndecan-4 KO) after LPS challenge. In line with syndecan-4 shedding promoting immune cell recruitment, expression of immune cell markers (CD8, CD11a, F4/80) and adhesion receptors (Icam1, Vcam1) were attenuated in syndecan-4 KO hearts after LPS. Cardiomyocytes and fibroblasts exposed to shed heparan sulfate-substituted syndecan-4 ectodomains showed increased Icam1, Vcam1, TNFα and IL-1β expression and NF-κB-activation, suggesting direct regulation of immune cell recruitment pathways. In cardiac fibroblasts, shed ectodomains regulated expression of extracellular matrix constituents associated with collagen synthesis, cross-linking and turnover. Higher syndecan-4 levels in the coronary sinus vs. the radial artery of open heart surgery patients suggested that syndecan-4 is shed from the human heart. Our data demonstrate that shedding of syndecan-4 ectodomains is part of the cardiac innate immune response, promoting immune cell recruitment, extracellular matrix remodeling and mitigating cardiac dysfunction in response to LPS. Highlights: Shedding of syndecan-4 ectodomains is part of the cardiac response to LPS challenge. Syndecan-4 shedding mitigates cardiac dysfunction after LPS challenge. Shed syndecan-4 ectodomains promote infiltration of immune cells to the heart. Shed syndecan-4 ectodomains regulate innate immune signaling and ECM remodeling. Syndecan-4 can be shed from the human heart.